Automated Microscopy: Macro Language Controlling a Confocal Microscope and its External Illumination: Adaptation for Photosynthetic Organisms - Steinbach, Gábor; Kaňa, Radek (Microscopy and microanalysis, 2016)
Photosynthesis research employs several biophysical methods, including the detection of fluorescence. Even though fluorescence is a key method to detect photosynthetic efficiency, it has not been applied/adapted to single-cell confocal microscopy measurements to examine photosynthetic microorganisms. Experiments with photosynthetic cells may require automation to perform a large number of measurements with different parameters, especially concerning light conditions. However, commercial microscopes support custom protocols (through Time Controller offered by Olympus or Experiment Designer offered by Zeiss) that are often unable to provide special set-ups and connection to external devices (e.g., for irradiation). Our new system combining an Arduino microcontroller with the Cell⊕Finder software was developed for controlling Olympus FV1000 and FV1200 confocal microscopes and the attached hardware modules. Our software/hardware solution offers (1) a text file-based macro language to control the imaging functions of the microscope; (2) programmable control of several external hardware devices (light sources, thermal controllers, actuators) during imaging via the Arduino microcontroller; (3) the Cell⊕Finder software with ergonomic user environment, a fast selection method for the biologically important cells and precise positioning feature that reduces unwanted bleaching of the cells by the scanning laser. Cell⊕Finder can be downloaded from http://www.alga.cz/cellfinder. The system was applied to study changes in fluorescence intensity in Synechocystis sp. PCC6803 cells under long-term illumination. Thus, we were able to describe the kinetics of phycobilisome decoupling. Microscopy data showed that phycobilisome decoupling appears slowly after long-term (>1 h) exposure to high light.
Keywords: remote controlled microscopy; osvětlení; Synechocystis; Microscopy, Confocal; laboratorní automatizace; software; confocal microscopy; Automation, Laboratory; automated microscopy; Software; photoprotection; photosynthetic membrane; konfokální mikroskopie; Lighting